Transfer znanja in socialni kapital v družbi znanja - Lenarčič, Blaž (Družboslovne razprave, 2007)
The article deals with the processes of the circulation, dissemination and application of scientific findings, which we term the transfer of knowledge. Given that the transfer of knowledge is a social action, the article points out that social capital is significant for its successful achievement. With the purpose of verifying this thesis, we present an analysis where the transfer of knowledge among producers and users in Slovenia was studied. The article concludes with an analysis of social capitalćs particular dimensions: structural, relational and cognitive.
Keywords: socialni kapital; družba znanja; knowledge; znanje; človeški kapital; prenos znanja